2006
DOI: 10.1007/s10750-006-0090-7
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and variability of River Habitat Survey features across Europe and the consequences for data collection and evaluation

Abstract: River Habitat Survey (RHS) data collected for the EU-funded STAR project was used to identify hydromorphological characteristic features of rivers in four European regions namely: lowlands; mountain; the Alps; and the Mediterranean. Using RHS attributes, Habitat Quality Assessment (HQA) -a measure of natural habitat diversity, and Habitat Modification Score (HMS) -a measure of anthropogenic modification, we identified considerable differences in frequency, diversity and evenness of features between the regions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 7 publications
1
45
1
Order By: Relevance
“…In some cases, alterations to channel geometry can also appreciably affect river morphology. These considerations agree with the findings of Szoszkiewicz et al (2006), according to whom the most typical modification found within EU rivers is bank re-sectioning. The percentage of bank reinforcement was also found to be one of the most important factors in describing morphological degradation in German rivers (Feld, 2004).…”
Section: Discussionsupporting
confidence: 91%
“…In some cases, alterations to channel geometry can also appreciably affect river morphology. These considerations agree with the findings of Szoszkiewicz et al (2006), according to whom the most typical modification found within EU rivers is bank re-sectioning. The percentage of bank reinforcement was also found to be one of the most important factors in describing morphological degradation in German rivers (Feld, 2004).…”
Section: Discussionsupporting
confidence: 91%
“…The RHS protocol has also been applied in a number of European countries and worldwide. Recently, during the EU co-funded STAR project, the application of RHS was widely adopted by 13 European Member States, in a total of 263 sites (Davy-Bowker and Furse 2006;Szoszkiewicz et al 2006). Further applications have been made in Poland with more than 600 sites studied (Szoszkiewicz, unpublished data) and outside of Europe (Manel et al 1999).…”
Section: Hydraulic Habitat and Lrdmentioning
confidence: 99%
“…950; Szoszkiewicz and Gebler 2011) than in the UK (ca. 20,000 sites; Szoszkiewicz et al 2006) and 26 river types distinguished in the country. This seriously reduces reliability of establishing reference conditions (defined by the conditions at the 20% of highest ranked sites; Raven et al 2002) and, consequently, also of calibration of hydromorphological conditions at particular sites against type-specific reference conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The set of hydromorphological parameters existing under undisturbed conditions may differ considerably between rivers in different physiographic settings (Kujanová et al 2016) and, thus, hydromorphological evaluation based on habitat quality index does not seem appropriate as in many rivers low richness or diversity of habitat features is natural and reflects naturally low morphological diversity of these rivers (Wy_ zga et al 2012b). Although the users of the RHS method notice various degrees of diversity of particular river habitat features in different regions (Szoszkiewicz et al 2006), they persist in using the index of habitat quality. The RHS method also uses habitat quality as one of the components in defining reference conditions for a particular river type.…”
Section: Methods Of Hydromorphological Assessment Used In Polandmentioning
confidence: 99%